Association of Endothelial Nitric Oxide Synthase Gene Polymorphisms with Susceptibility to Prostate Cancer: a Comprehensive Systematic Review and Meta-Analysis - Abedinzadeh, Mehdi; Dastgheib, Seyed Alireza; Maleki, Hadi; Heiranizadeh, Naeimeh; zare, Mohammad; Jafari-Nedooshan, Jamal; Kargar, Saeed; Neamatzadeh, Hossein (Urology Journal, 2020)
Purpose: A variety of studies have evaluated the association of polymorphisms at endothelial nitric oxide synthase (eNOS) gene with risk of prostate cancer. However, the results remain inconclusive. This meta-analysis was performed to derive a more precise estimation between eNOS polymorphisms and prostate cancer risk. Materials and Methods: A comprehensive literature search was conducted using PubMed, EMBASE, Wed of Science, Elsevier, Cochrane Library, SciELO, SID, WanFang, VIP, CBD and CNKI database up to March 20, 2020. Odds ratios with 95% confidence intervals were used to assess the strength of the associations. Results: A total of 22 case-control studies including 12 studies with 4,464 cases and 4,347 controls on +894G>T, five studies with 589 cases and 789 controls on VNTR 4a/b, and five studies with 588 cases and 692 controls on -786T > C were selected. Overall, pooled data showed a significant association between eNOS 894G>T, VNTR 4a/b, and -786T > C polymorphisms and an increased risk of prostate cancer in the global population. When stratified by ethnicity, a significant association was found between eNOS +894G>T and -786T>C polymorphisms and risk of prostate cancer in Caucasians. Conclusion: Our results indicated that eNOS 894G>T, VNTR 4a/b, and -786T>C polymorphisms were associated with risk of prostate cancer in the global population as well as Caucasian population.